Reducing Congestion in Obstructed Highways with Traffic Data Dissemination Using Ad hoc Vehicular Networks. (25th July 2010) - Hewer, Thomas D.; Nekovee, Maziar; Coveney, Peter V.
Abstract : Vehicle-to-vehicle communications can be used effectively for intelligent transport systems (ITSs) and location-aware services. The ability to disseminate information in an ad hoc fashion allows pertinent information to propagate faster through a network. In the realm of ITS, the ability to spread warning information faster and further is of great advantage to receivers. In this paper we propose and present a message-dissemination procedure that uses vehicular wireless protocols to influence vehicular flow, reducing congestion in road networks. The computational experiments we present show how a car-following model and lane-change algorithm can be adapted to "react" to the reception of information. This model also illustrates the advantages of coupling together with vehicular flow modelling tools and network simulation tools.